Callus and shoot induction of leaf culture Lilium longiflorum with NAA and BAP - kadek dwipayani lestari; NI WAYAN DESWINIYANTI; IDA AYU ASTARINI; LUH MADE ARPIWI (Smujo International, 2019)
Abstract. Lestari NKD, Deswiniyanti NW, Astarini IA, Arpiwi NLM. 2019. Callus and shoot induction of leaf culture Lilium longiflorum with NAA and BAP. Nusantara Bioscience 11: 162-165. Lilium longiflorum Thunb., an Easter lily, is a common ornamental plant used as potted plant, cut flower, cosmetic and medicine. The research on tissue culture technique to induce shoots and callus is expected to increase the yield of lilies quickly and efficiently. This study aims to determine the effect of plant growth regulator combination of Naphthalene Acetic Acid (NAA) and Benzyl Amino Purine (BAP) on the development of leaf culture and the best concentration for callus induction and shoots of lily plants. This study was conducted in a completely randomized design using leaf explants in Vacin and Went medium, with combination of NAA and BAP (0; 0.5; 1 mg..L-1 ) as the treatments. The result of the eight-week observations shows that the plant growth regulators significantly affected either in days initiation callus, days initiation of shoot, percentage of callus, percentage of shoot, diameter of callus, no of shoot and length of shoot. The combination of 1 mg.L-1 NAA and BAP had the best effect in the percentage of explants forming shoots (100%), means number of shoots (5.8), and means length of shoot (11.6 cm).